Prevention and early detection of the most aggressive skin cancer: melanoma - Szostak, Agata Paulina; Szopińska, Kinga; Graca, Magdalena; Śmigielska-Mikołajczyk, Maria Janina; Łowicka, Weronika; Dyląg, Liliana; Wawszkowicz, Konrad; Oluszczak, Karolina; Szeliga, Anna; Korta, Karolina (Quality in Sport, 2024)
Skin cancers are the most common cancers and they are divided into two types: melanoma and non-melanoma skin cancers (NMSCs). Melanoma is the most lethal and aggressive type of skin cancer. The incidence of this type of cancer is increasing. Mortality from melanoma can be reduced by avoidance of exposure to ultraviolet radiation and regular skin examination. Materials and methods of research English-language scientific literature available in the PubMed and Google Scholar databases was reviewed using the following keywords: ”melanoma”; ”early-detection”; ”self-screening”; ”tanning”; ”sunscreen”; ”dermatoscopy”; ”mortality”; ”prevention”; ”risk-factors”; ”UV protection”; ”epidemiology”. Aim of the study The purpose of this narrative review is to present risk factors, prevention and the importance of early detection of melanoma. This review also shows that it is possible to increase people’s awareness of skin self-examination and the importance of UV protection through the use of modern technology (text messaging). Conclusions There are many risk factors for melanoma. People’s awareness of the risks of UV exposure from both sunbathing and tanning beds is increasing. More and more people are starting to protect themselves from the sun and regularly check their skin. This behavior reduces the risk of developing melanoma and increases the chances of detecting melanoma in its early stages.